Underwater Shock Response Analysis of a Floating Vessel - J.E. van Aanhold; G.J. Meijer; P.P.M. Lemmen (Shock and Vibration)
The response of a surface vessel to underwater shock has been calculated using an explicit finite element analysis. The analysis model is two-dimensional and contains the floating steel structure, a large surrounding water volume and the free surface. The underwater shock is applied in the form of a plane shock wave and cavitation is considered in the analysis. Advanced computer graphics, in particular video animations, provide a powerful and indispensable means for the presentation and evaluation of the analysis results.